Demystified …: Microsatellites. Issue 4 (1st August 2000) - Bennett, P
Abstract : Microsatellite DNA sequences consist of relatively short repeats of one to five base pair units; together with satellites and minisatellites they comprise a larger family known as tandemly repetitive sequences. Microsatellites are found both in prokaryotes and eukaryotes, including humans, wherein they appear scattered almost at random throughout the genome. Although in prokaryotes distinct biological functions have been demonstrated, the role of microsatellites in eukaryotes is less clear. Nevertheless, several interesting hypotheses exist suggesting that certain microsatellites may exert subtle influences on the regulation of gene expression. Although the presence of these subtle mechanisms may be beneficial to a whole population, when they go wrong, as is thought to happen in the case of human trinucleotide repeat associated diseases, such as Huntington's disease, the consequences for the individual can be fatal. Most human microsatellites probably have no biological use at all; however, they are extremely useful in such fields as forensic DNA profiling and genetic linkage analysis, which can be used to search for genes involved in a wide range of disorders. With a primary focus on humans, it is the aim of this review to present an up to date discussion, both of the biological aspects and scientific uses of microsatellite sequences. In the latter case, basic theoretical and technical points will be considered, and as such it may be of use both to laboratory and non-laboratory based readers.